Reassessing LPDB’s Strategic Readiness for 2025–2029: A Case-Based Strategic Diagnosis Integrating Public-Sector Governance and Strategic Management Frameworks - Hardy R Hermawan; Mardiana Purwaningsih (Administratio, 2025)
This research examines the strategic readiness of LPDB-KUMKM in implementing its 2025–2029 business transformation roadmap. Using a qualitative case study approach supported by PESTEL, McKinsey’s 7S, SWOT, IFE, EFE, IE, and TOWS analyses, the study explores strategic alignment, organizational capacity, and external opportunity structures. The data were drawn from institutional documents, policy inputs, and non-direct interview insights designed to capture perspectives from internal stakeholders. Findings show that LPDB holds significant growth opportunities driven by national cooperative policy, digital finance expansion, and emerging green and Islamic financing sectors. However, internal challenges persist, including uneven HR competence, limited ESG assessment capability, cooperative literacy gaps, and the need for stronger digital and risk governance systems. The IE matrix positions LPDB in the Grow and Build quadrant, indicating that strategic expansion is viable if balanced with capability strengthening. The TOWS mapping further suggests scenario pathways emphasizing digitalization, green financing, partnership models, and human capital development. This study contributes to public finance literature by demonstrating how institutional transformation in government financial agencies requires phased implementation, ecosystem support, and alignment between strategy ambition and operational capacity.